Use of corn- and sorghum-based distillers dried grains with solubles in diets for nursery and finishing pigs - Feoli, Carolina (Kansas State University, 2008)
Twelve experiments were completed to evaluate corn- and sorghum-distillers dried grains with solubles (DDGS) in diets for nursery and finishing pigs. In Exp. 1, corn-DDGS had 223 kcal/kg greater DE than sorghum-DDGS (P<0.02). In Exp. 2, pigs fed a corn-soy control diet had greater ADG, nutrient digestibility, HCW, and dressing percentage (P<0.02) and lower iodine value (IV) of jowl fat (P<0.001) than pigs fed diets with 40% DDGS. High-energy DDGS supported lower ADG, ADFI, and digestibility of DM (P<0.06) than moderate-energy DDGS, and sorghum-DDGS resulted in lower IV than corn-DDGS (P<0.001). In Exp. 3 and 4, addition of sodium bicarbonate to adjust dietary pH and electrolyte balance did not improve growth performance in nursery or finishing pigs (P>0.16) and adding molasses to improve palatability decreased (P<0.05) G:F for finishing gilts. In Exp. 5 and 6, enzyme additions improved nutrient digestibility in nursery (P<0.04) and finishing (P<0.01) pigs fed diets with high inclusion of DDGS. In Exp. 7, expander processing improved (P<0.02) ADG, G:F, and digestibility of DM, N, GE, and cellulose compared with standard steam conditioning of diets for nursery pigs, with the greatest response in G:F for pigs fed sorghum-DDGS (DDGS source × conditioning; P<0.02). In Exp. 8 and 9, expander conditioning improved G:F and dressing percentage (P<0.007) and digestibility of DM, N, and GE compared with standard conditioning (P<0.02), with the greatest response in digestibility of DM for the DDGS diets (diet × conditioning, P<0.01). In Exp. 10, 11, and 12, increasing tallow from 0 to 5% in diets with 40% DDGS improved (P<0.05) G:F. Dressing percentage was improved with addition of tallow and palm oil (P<0.08), but IV become worse (linear, P<0.06) as tallow was increased in the diet. Adding coconut oil improved growth performance and carcass firmness in pigs fed diets with 40% DDGS (P<0.01). In conclusion, growth performance and nutrient digestibility decreased with addition of DDGS to diets for nursery and finishing pigs. However, adding enzymes partially restored nutrient digestibility; expander conditioning improved G:F, dressing percentage, and nutrient digestibility; and adding coconut oil to diets with 40% DDGS improved G:F and carcass firmness.
Keywords: DDGS; Distillers dried grains; Pig; Growth performance; Carcass characteristics; Sorghum; Agriculture, Animal Culture and Nutrition (0475)